Self Disclosure Anak Broken Home Melalui Media Sosial TikTok : Studi Deskriptif Followers TikTok di Halaman Komentar Konten @AKUISANN - Cyntia Dewi Anggraini; Azizah Des Derivanti; Miftia Andini (Jurnal Ilmiah Mahasiswa Komunikasi (JIMaKom), 2022)
The purpose of this study is to find out how the self- disclosure process is carried out by TikTok followers on the comments page on @akuisann content. This study uses qualitative methods, descriptive studies, interpretive paradigms, triangulation of sources and in-depth interviews with 5 informants who were selected based on the characteristics or criteria determined by the researcher (Purposeful Sampling). The results of the study reveal that self-disclosure carried out by informants through the comments page on @akuisann content based on the Johari Window Theory belongs to two areas, namely open areas and hidden areas. @akuisann's content for commenting is that there is a dyadic effect where informants do self-disclosure because they see many people doing the same thing. In addition, the results of the description of the informants have a desire to motivate each other. The benefits that result is a feeling of relief because he has conveyed what he experienced to others who have a similar fate. Meanwhile, the communication privacy management process is carried out with culture contextual, motivational, and risky backgrounds. Keywords : Self Disclosure, TikTok, Social Media, Johari Window Theory, Teori Communication Privacy Management (CPM)